Newborn screening for severe combined immunodeficiency in Malaysia: current status, challenges and progress - Chang, Wai Leng; Mohd Noh, Lokman; Abdul Latiff, Amir Hamzah; Woo, Kent Chee Keen; Ismail, Intan Hakimah; Abd Hamid, Intan Juliana; Siniah, Sangeetha; Zainal Abidin, Mohd Azri; Sham, Marina; Mat Ripen, Adiratna; Baharin, Mohd Farid; Abdul Wahab, Asrul; et al. (Frontiers in Immunology, 2024)
Introduction: Early diagnosis of Severe Combined Immunodeficiency (SCID) increases survival outcomes and quality of life while significantly minimizing healthcare burden and costs. Despite growing evidence supporting the benefits and cost-effectiveness of SCID detection through newborn screening (NBS), it has yet to be implemented in Malaysia. This study aims to explore experts’ opinions on the current status, challenges, and crucial strategies needed for the successful implementation of SCID NBS. Methodology: A guided, structured interview was employed to explore opinions on the current status, barriers, and strategies for implementing SCID NBS in Malaysia. All 13 invited experts participated in this study, indicating complete participation from the entire Malaysian immunology fraternity (consisting of eight clinical immunologists and five immunopathologists). Key Findings: Several initiatives are ongoing to establish SCID NBS in Malaysia. Hindrances such as low immunologist-to-patient ratio, unequal placements of immunologists throughout Malaysia, society’s low disease awareness, national health prioritization, lack of stakeholder engagement, and inadequacy of local study/data were highlighted. Pilot research on SCID NBS, advocacy workshops, and promotion materials are among the ongoing activities outlined in the blueprint, paving the way for this nationwide NBS program to be achievable in the near future. Conclusion: This article provides recommendations to policymakers in mandating SCID NBS. Strategies by key stakeholders are underway, particularly in advocacy programs and efforts to increase awareness among clinicians and the public.